2018
DOI: 10.3233/jbr-180316
|View full text |Cite
|
Sign up to set email alerts
|

Wild Andean blackberry (Rubus glaucus Benth) and Andean blueberry (Vaccinium floribundum Kunth) from the Highlands of Ecuador: Nutritional composition and protective effect on human dermal fibroblasts against cytotoxic oxidative damage

Abstract: BACKGROUND: Andean blackberries (Rubus glaucus Benth) and Andean blueberries (Vaccinium floribundum Kunth) are wild berries consumed and commercialised by the indigenous people of the Andean regions of Ecuador. OBJECTIVE: This study aims to determine the chemical composition and the ability of A. blackberries and A. blueberries to protect human dermal fibroblast (HDFa) against cytotoxic oxidative damage. METHODS: Total phenolic, flavonoid, anthocyanins and tannins content were determined spectrophotometrically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
1
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 44 publications
3
26
1
4
Order By: Relevance
“…The results shown here agree with a large number of reports that have shown the protective effect of the polyphenols present in fruits against free-radical-mediated cell damage [24,44,46]. In particular, the results presented here add to the previous reports that show similar properties in other fruits consumed in Ecuador, such as capulí [5], and wild Andean blackberry and blueberry [4]. Several studies have demonstrated the positive effects of plant bioactive compounds, such as polyphenols, in modulating the activity of diverse antioxidant enzymes (GPx GR, GST, SOD and catalase) by reducing the damage induced by AAPH and other different stressors and restoring conditions similar to control levels in HDFa [47][48][49].…”
Section: Protective Effect Of Pechiche Extract Against Oxidative Cytosupporting
confidence: 91%
See 3 more Smart Citations
“…The results shown here agree with a large number of reports that have shown the protective effect of the polyphenols present in fruits against free-radical-mediated cell damage [24,44,46]. In particular, the results presented here add to the previous reports that show similar properties in other fruits consumed in Ecuador, such as capulí [5], and wild Andean blackberry and blueberry [4]. Several studies have demonstrated the positive effects of plant bioactive compounds, such as polyphenols, in modulating the activity of diverse antioxidant enzymes (GPx GR, GST, SOD and catalase) by reducing the damage induced by AAPH and other different stressors and restoring conditions similar to control levels in HDFa [47][48][49].…”
Section: Protective Effect Of Pechiche Extract Against Oxidative Cytosupporting
confidence: 91%
“…Total carotenoids and vitamin C content in pechiche fruits were analyzed and are shown in Table 1. The pechiche fruits showed low values of carotenoids compared with other Ecuadorian fruits [4][5][6] and tropical fruits from the region [33,34] and based on intake recommendations for carotenoids [35], whereas in the case of vitamin C, the values were within the previously reported range [6,33,34]. Pechiche fruits could be classified within the group of fruits with low vitamin C content (< 30 mg/100 g of FW) according to the classification previously proposed by Ramful et al [36].…”
Section: Bioactive Compoundsmentioning
confidence: 67%
See 2 more Smart Citations
“…Andean blackberry and Andean blueberry fruits attenuated the oxidative damage elicited in human dermal HDFa fibroblasts by the stressor 2,2'-azobis(2-amidinopropane) dihydrochloride, suggesting these results promising benefits for the prevention of oxidative damage and skin injury (Alarcón- Barrera et al, 2018). Moreover, the improvement in the fibroblast functionality and, in turn, in the cell migration exerted by extracts prepared from berries such as strawberry and blackberry and from black soybean seed coasts (Nizamutdinova et al, 2009) were associated with the phenolic compounds, specifically with the anthocyanins.…”
Section: Changes In Skin Fibroblast Migrationmentioning
confidence: 99%